IMPLEMENTATION OF CHILD-FRIENDLY SCHOOLS IN DEVELOPING THE CHARACTER OF PANCASILA STUDENT PROFILES IN THE MERDEKA CURRICULUM - Tirtoni, Feri (Journal of Higher Education and Academic Advancement, 2024)
Child Friendly School is a program to create a school environment that is peaceful, comfortable, and supportive of children's development. The program aims to improve the quality of education and character building of students by taking into account psychological and social aspects. Knowing the purpose of this research can provide valuable information for the development of educational programs and policies in the future. This researcher used a qualitative method using descriptive analysis. The method of writing this article uses data collection techniques obtained through observation, interviews, and documents. This research focuses on child-friendly schools in character development. The results of this research on SDN Kebangsaan 1 have made several efforts to create a child-friendly school including child rights-based curriculum documents, SDN Kebangsaan 1 has a learning design policy that prioritizes children's rights and builds the character of Pancasila student profiles